(untitled) (Altre Modernità, 2021)
Sara Soncini, Le metamorfosi di Sarah Kane: 4.48 Psychosis sulle scene italiane (Pisa, Pisa University Press, 2020, 144 pp. ISBN 978-883339-3735) di Mariacristina Cavecchi